Improving the Use of Digital Technologies in Science Teaching (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article talks about the aspects of improving the use of digital technologies in the teaching of natural sciences in primary grades of general secondary schools.